An Optimal Lights Layout Scheme for Visible-Light Communication System - Ding Deqiang; Ke Xizheng; Xu Linpeng (2007 8th International Conference on Electronic Measurement and Instruments, 2007)
The visible-light communication is a novel kind of optical wireless communication utilizing the white LEDs. As compared with infrared indoor communication this system has high radiation power to enable high quality of service for the light is "visible". Generally, there are several plural lights installed in a room for sufficiently illuminating. So the layout of lights determining the distribution of received power is a key problem affecting the performance of visible light communication system. In this paper, the relation between the layout of lights and received power is studied and a best scheme is proposed to solve the design of lights layout, which is identified by simulation.